Seasonally comparative study of biological characteristics the Yellowstripe scad - Selaroides leptolepis (Cuvier, 1833) in the coastal area of Binh Thuan province - Van Hau, Le; Thanh Nam, Nguyen; Xuan Huan, Nguyen (VNU Journal of Science: Natural Sciences and Technology; Vol 33 No 2S, 2017)
Obtained results based on analysing 270 fished individuals of the yellowstripe scad – Selaroides leptolepis that were collected during 2 phases of field work (1 st : 23/9 – 5/10/2013 with 150 individuals; 2 nd : 26/3/2017 with 120 individuals) in the cosatal area of Binh Thuan province show that: The length of caught fishes ranged from 92 to 160 mm but mainly from 115 to 130 mm in length and from 8 to 55 gr but mainly from 18 to 40 gr in weight. Growth parameters of  the yellowstripe scad stock are as follows: L ¥ = 192.89 mm, W ¥ = 73.46 gr,  k = 0.586, t o = - 0,603 and b = 2.92.  Its weight – length relationship takes the form of W = 2,25 x 10 -6 x L 2,92 (r = 0,89). Fishes caught included three age groups of 1 + , 2 + and 3 + but focusing on the age group 1 + (1 st : 56.67%; 2 nd : 49.43%). Main food components of the yellowstripe scad are Macura, Copepoda, Ostacoda and Amphipoda. Sexual maturity of exploited fish individuals is low, mainly on the stage I, II and III, no individuals at the stage V, VI.